(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study is an attempt to examine the gender influence on personality dimensions of late adolescence belongs to Meerut city, Uttar Pradesh. Total 156 late adolescence (73 males/83 females) age 17 to 19 years were purposively drawn from different colleges of Meerut city. Personality Inventory constructed by Dr. Y. Singh and Dr. H.M. Singh [1] was applying for data collection. Mean, SD, ‘t’ Test was computed for data statistical analysis. Findings reported that gender influence has no significant difference reveal in personality and its dimensions among late adolescence belongs to Meerut, city Uttar Pradesh.